PENGEMBANGAN MEDIA MONOPOLI DALAM PEMBELAJARAN SENI BUDAYA UNNTUK SISWA KELAS IV SEKOLAH DASAR - Reski Dwi Yuliana, Andi; Ahmad Syawaluddin; Bhakti Prima Findiga Hermuttaqien (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the limited availability of learning media for Cultural Arts, resulting in insufficient understanding among fourth-grade students, as well as the need for differentiated learning to accommodate student diversity. The study aimed to develop and assess the feasibility of a Monopoly media using the Research and Development (R&D) ADDIE model, which was implemented among fourth-grade students at UPTD SDN 48 Barru. The analysis phase involved teacher interviews, followed by planning the media design and instruments. The development stage included media production, validation by material and media experts, and revisions until the product reached the